Modified pid control design for roll fin actuator of nonlinear modelling of the fishing boat - Alarcin, Fuat; Demirel, Hakan; Su, M. Ertugrul; Yurtseven, Ahmet (GDANSK UNIV TECHNOLOGY, 2014)
This study aims to reduce roll motion of a fishing boat which arises from disturbing hydrodynamic effects by means of fin roll stabilizer. It is assured that roll motion with nonlinear damping and restoring moment coefficients are down to the desired level through classical PID and modified PID algorithms. At the time of sailing, stability, a very important concept, was examined using Lyapunov direct method taking initial conditions into consideration, and it was noted that the system was generally stable. In addition, NACA 0015 model was used for the fin roll stabilizer, and flow analysis was carried out with Computational Fluid Dynamics (CFD) method. In the simulation results, when the same gains were used, modified PID controller algorithms were relatively more effective compared to PID in the fin roll stabilizer system.
Keywords: stability analyses; nonlinear roll motion; modified PID; CFD; Engineering